2023
DOI: 10.1111/aogs.14580
|View full text |Cite
|
Sign up to set email alerts
|

Different subtypes of ultrasound‐diagnosed adenomyosis and in vitro fertilization outcomes: A systematic review and meta‐analysis

Abstract: Introduction Adenomyosis prevalence among women with infertility is increasing; their management during in vitro fertilization is usually based on ultrasound diagnosis alone. Herein, we summarize the latest evidence on the impact of ultrasound‐diagnosed adenomyosis on in vitro fertilization outcomes. Material and methods The study was registered with The International Prospective Register of Systematic Reviews (CRD42022355584). We searched PubMed, Embase, and Cochrane Library databases from inception to Januar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 33 publications
0
5
0
Order By: Relevance
“…In the literature, a recent retrospective study reported that patients with focal adenomyosis or with tubal infertility may have better reproduction outcomes compared with patients with diffuse adenomyosis following an embryo transfer with an ultra-long GnRH agonist protocol [ 20 ]. Similarly, a recent meta-analysis reported that diffuse adenomyosis had an adverse impact on in vitro fertilization outcomes, resulting in lower live birth and clinical pregnancy rates, while the miscarriage rates remained unchanged [ 21 ]. Furthermore, other data show that an increase in uterine volume can negatively affect reproductive outcomes in patients with adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In the literature, a recent retrospective study reported that patients with focal adenomyosis or with tubal infertility may have better reproduction outcomes compared with patients with diffuse adenomyosis following an embryo transfer with an ultra-long GnRH agonist protocol [ 20 ]. Similarly, a recent meta-analysis reported that diffuse adenomyosis had an adverse impact on in vitro fertilization outcomes, resulting in lower live birth and clinical pregnancy rates, while the miscarriage rates remained unchanged [ 21 ]. Furthermore, other data show that an increase in uterine volume can negatively affect reproductive outcomes in patients with adenomyosis.…”
Section: Discussionmentioning
confidence: 99%
“…Another retrospective study, conducted by Li et al, shared the same conclusion and suggested that a uterine volume of more than 98.81 cm 3 might lead to a lower live birth rate due to a higher incidence of miscarriage [ 23 ]. On the other hand, Wang et al reported that symptomatic adenomyosis was found to affect live birth, clinical pregnancy, and miscarriage rates, while asymptomatic adenomyosis may not have a significant impact on pregnancy outcomes [ 21 ]. However, to date, no studies have investigated the influence of different subtypes of adenomyosis diagnosed using the MUSA criteria on reproductive outcomes.…”
Section: Discussionmentioning
confidence: 99%
“… 4 , 5 , 6 More data regarding the prevalence and characteristics of adenomyosis, as diagnosed by noninvasive methods in subfertile women, is needed. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…Studies that describe the prevalence of different ultrasonographic adenomyosis features in subfertile women, adhering to standardized diagnostic criteria, would facilitate further studies on the potential impact on fertility and ART outcome. 7 , 8 …”
Section: Introductionmentioning
confidence: 99%
“…We recently read an article by Wang et al in Acta Obstetricia et Gynecologica Scandinavica . 1 The authors reviewed the available literature to quantitatively assess the impact of adenomyosis diagnosed by ultrasound on the outcome of in vitro fertilization. 1 However, this study may have some methodological flaws.…”
mentioning
confidence: 99%